Gains from the transition from face-to-face to digital/online modality to improve education in emergency - Camacho-Zuñiga, Claudia; Peña-Becerril, Maritza; Cuevas-Cancino, Maria de la O; Avilés-Rabanales, Eréndira Gabriela (Frontiers in Education, 2023)
Education during emergencies demands attention from both institutions and governments, as the incidence of disasters and crises continues to increase worldwide due to various challenges that threaten humanity, including climate change, terrorism, food and water scarcity, energy crises, poverty, and inequality. Emergency remote teaching (ERT) is a critical factor in providing academic opportunities, building resilience, and promoting recovery for affected individuals. This research examines the challenges associated with transitioning from face-to-face to online/digital lessons, according to the perceptions of 105 professors in a Mexican private university, 2 months after mandatory online/digital teaching was implemented. By analyzing data collected through a survey using statistical and data mining techniques, we identified factors that should be considered when designing future education in emergency situations. The study found that while most professors positively evaluated their performance in ERT, they still preferred face-to-face teaching due to the lack of personal interaction and distractions. Professors adapted to ERT with technological training provided by the institution, but reported an increase in workload and the importance of the balance between job responsibilities and family issues. The study also revealed that professors’ performance in ERT depended on the conditions of their teaching space at home. Furthermore, the study suggested the need for the development of an improved assessment framework for online evaluation methods, and integration of the most effective online and face-to-face teaching strategies for everyday academic contexts. The sudden change in education modality represented a fantastic opportunity to introduce teaching-learning-evaluating strategies and technologies while forcing institutions to evolve into the digital environment. Therefore, every education stakeholder should identify and implement best practices of the online and face-to-face modalities to improve future education in emergencies.